Strategi Cooperative Learning dalam Meningkatkan Mutu Pembelajaran Tematik - Rofiatun Nisa'; Ika Aryastuti Hasanah; Irawati (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2021)
To ensure learning goes well, appropriate and appropriate strategies are needed in the learning process, so it is hoped that the learning objectives and targets desired by the teacher in order to improve the quality of thematic learning can be achieved properly. The objectives of this study were to: find out the teacher's strategic planning in improving the quality of thematic learning, to describe the implementation of teacher strategies in improving the quality of thematic learning, to describe the results and to evaluate the teacher's strategy in improving the quality of thematic learning in class V MI Muhammadiyah 10 Pesanggrahan. This research uses a qualitative approach with descriptive research type. Data collection was carried out using the method of observation, interviews, documentation. Data analysis techniques used: data reduction, data presentation and conclusion. The results showed that: (1) There is a learning plan in the form of consideration in the selection of strategies, methods and learning media that are tailored to the material and needs of students, besides that there are supporting programs for teachers, namely participating in workshops. (2) The strategy of class V teachers in improving the quality of learning is the cooperative learning strategy. (3) The result of the cooperative learning strategy in improving the quality of thematic learning in class V is that the results of the assessment are always increasing for each sub-theme.